Microsomal antibodies in active chronic hepatitis and other disorders - Rizzetto, M. (1973)
An autoantibody reacting with microsomal membranes has been characterized by a distinctive immunofluorescence pattern on proximal renal tubules and hepatocytes. The microsomal nature of the antigen was demonstrated by absorption and quantitative complement fixation studies. These results showed the antibodies to be quite distinct from the mitochondrial antibodies found in primary biliary cirrhosis. Microsomal antibodies have so far been detected in sixteen cases, of whom twelve had liver disorders. These antibodies, although rare, may provide a serological marker for a small proportion of active chronic hepatitis cases differing in several respects from other recognized subgroups in this disease.